Pengaruh Tinggi Pasir Terhadap Penentuan Nilai Permeabilitas Pasir - Dadang Mh B; Dewi Chandra RG, Dadang Mh B RG (Jurnal Poli-Teknologi, 2010)
A mold with sand casting consists activities such as placing a pattern in the sand to form the cavity, making the canal system, filling the cavity with molten metal which is still able to be solidified, dismantle mold casting product containing and cleaning castings. Until now, the sand mold casting process is still the first choice of foundry industries especially for small industries, the products are widely used for cylinder blocks and drain pipes, the quality of the casting is influenced by permeability. Permeability is the measure of whether a medium pore easily passed by the fluid. Permeability of the sand indicates the ability of sand in the water escape. The structure and texture as well as other organic elements took part in raising the rate of permeability of the sand. The sand with high permeability increase infiltration rate and thus, reduce the rate of water flow. In making this sand permeability test equipment used design concept consisting U. Tube Manometers Instrument Stand Pipe compactor, speciment Holder, Flowmeter, Air Pressure Regulator, Frame, Hose Connector, Hose Connector to the compressor, the air volume of 2000 liters given, test results showed that the greater height of the sand the greater the value of permeability. Any additional height by 1 cm sand, will increase the value of permeability of sand around 0.04 until 0.0693. Keyword: Value of Permeability of Sand Abstrak Cetakan dengan pengecoran pasir melibatkan kegiatan seperti menempatkan pola dalam kumpulan pasir untuk membentuk rongga cetak, membuat sistem saluran, mengisi rongga dengan pencetakan logam cair, yang memungkinkan logam cair untuk membekukan, membongkar cetakan pengecoran produk yang mengandung dan pembersihan coran. Sampai saat ini, proses pengecoran cetakan pasir masih merupakan andalan industri pengecoran terutama industri kecil, produk yang banyak digunakan untuk blok silinder dan pipa saluran, kualitas pengecoran dipengaruhi oleh permeabilitas. Permeabilitas adalah ukuran pori-pori media apakah mudah dilewati oleh fluida. Permeabilitas pasir menunjukkan kemampuan pasir di air keluar. Struktur dan tekstur serta unsur organik lainnya ikut ambil bagian dalam menaikkan laju permeabilitas pasir. Pasir dengan kenaikan permeabilitas laju infiltrasi yang tinggi dan dengan demikian, mengurangi laju aliran air. Dalam pembuatan alat uji permeabilitas pasir menggunakan konsep desain yang terdiri U. Tube manometer Stand Instrumen pemadat Pipa, spesimen Holder, flowmeter, Air Regulator Tekanan, Frame, Hose Connector, Hose Konektor ke kompresor, volume udara tahun 2000 liter yang diberikan, hasil tes menunjukkan bahwa tinggi lebih besar dari pasir besar nilai permeabilitas. Setiap ketinggian tambahan dengan pasir 1 cm, akan meningkatkan nilai permeabilitas pasir sekitar 0,04 sampai 0,0693. Kata Kunci: Nilai Permeabilitas Pasir